2020
DOI: 10.3390/microorganisms8060960
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Activities of Probiotic Lactobacilli on Antibiotic-Resistant Proteus mirabilis

Abstract: The emergence of biofilm-forming, multi-drug-resistant (MDR) Proteus mirabilis infections is a serious threat that necessitates non-antibiotic therapies. Antibiotic susceptibility and biofilm-forming activity of P. mirabilis isolates from urine samples were assessed by disc diffusion and crystal violet assays, respectively. Antimicrobial activities of probiotic Lactobacilli were evaluated by agar diffusion. Antibiofilm and anti-adherence activities were evaluated by crystal violet assays. While most P. mirabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…This relatively agreed with El-Mokhtar et al [36] who reported susceptibility of Klebsiella to PROBIOTICS' filtrates with zones of inhibition average in-between 12.2 and 21.1 mm and 11.3 and 16.1mm for susceptibility of pseudomonas. While Heshmatipour et al [37] reported the susceptibility of E. coli with zones of inhibition average in-between [14 and 20 mm] and Shaaban et al [38] who reported the greater activity against multi-drug resistant proteus with 21 mm zones of inhibition. In addition to Chen et al [39] who reported the greatest activity against 21 strains of carbapenem-resistant E. coli and for 9 strains of carbapenem-resistant k. pneumonia with zones of inhibition greater than 15 mm.…”
Section: Discussionmentioning
confidence: 99%
“…This relatively agreed with El-Mokhtar et al [36] who reported susceptibility of Klebsiella to PROBIOTICS' filtrates with zones of inhibition average in-between 12.2 and 21.1 mm and 11.3 and 16.1mm for susceptibility of pseudomonas. While Heshmatipour et al [37] reported the susceptibility of E. coli with zones of inhibition average in-between [14 and 20 mm] and Shaaban et al [38] who reported the greater activity against multi-drug resistant proteus with 21 mm zones of inhibition. In addition to Chen et al [39] who reported the greatest activity against 21 strains of carbapenem-resistant E. coli and for 9 strains of carbapenem-resistant k. pneumonia with zones of inhibition greater than 15 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of LPS in circulation may increase risk of atherosclerosis ( 102 ). While L. casei has been shown to destroy the biofilm of Proteus mirabilis P14 to avoid damage to the gut barrier ( 103 ).…”
Section: Probiotics Diversely Involved In Lipid Metabolism To Improve...mentioning
confidence: 99%
“…Kaur et al (2018) showed that the antibiofilm efficacy of seven strains of Lactobacillus against Vibrio cholerae biofilm was more than 90%. Shaaban et al (2020) found that Lactobacillus casei and Lactobacillus reuteri could destroy the multidrug-resistant Proteus mirabilis biofilm, representing a worthwhile alternative treatment. Another study revealed the inhibitory effect of LAB and other probiotics strains on planktonic and biofilm of dental bacteria (Ben Taheur et al, 2016).…”
Section: Competitive Exclusion (Probiotics)mentioning
confidence: 99%